2005
DOI: 10.1037/h0087467
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of the Contingent Spatial Blink.

Abstract: Attentional capture is the unintentional deployment of attention to a task-irrelevant but attentionally salient object. The contingent involuntary orienting hypothesis states that it occurs only if a distractor's property matches current top-down attentional control settings (Folk, Remington, & Johnston, 1992). Folk, Leber, and Egeth (2002) found that monitoring a central RSVP stream for a coloured target led to spatial attentional capture by a peripheral distractor that matched the target colour. Using a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
5
21
1
Order By: Relevance
“…Bonferronicorrected t tests revealed that the absence of a face was reported more accurately than were neutral and fearful faces [t(13) 5.38, p 3 .0005, and t(13) 5.11, p 3 .0005, Yi, and Chun (2004), who found no reduced scene detection performance in an AB paradigm when neutral faces could be ignored. Studies investigating the effect of neutral distractor stimuli in RSVP series have demonstrated that only distractor items precisely matching the participants' attentional set, as given by the target-defining feature, can trigger attentional capture (Folk, Leber, & Egeth, 2002;Lamy, Leber, & Egeth, 2004;Leblanc & Jolicoeur, 2005;Maki & Mebane, 2006). In the present experiments, faces did not share features with the scene target and, therefore, did not induce attentional capture in Experiment 3.…”
Section: Methodscontrasting
confidence: 51%
“…Bonferronicorrected t tests revealed that the absence of a face was reported more accurately than were neutral and fearful faces [t(13) 5.38, p 3 .0005, and t(13) 5.11, p 3 .0005, Yi, and Chun (2004), who found no reduced scene detection performance in an AB paradigm when neutral faces could be ignored. Studies investigating the effect of neutral distractor stimuli in RSVP series have demonstrated that only distractor items precisely matching the participants' attentional set, as given by the target-defining feature, can trigger attentional capture (Folk, Leber, & Egeth, 2002;Lamy, Leber, & Egeth, 2004;Leblanc & Jolicoeur, 2005;Maki & Mebane, 2006). In the present experiments, faces did not share features with the scene target and, therefore, did not induce attentional capture in Experiment 3.…”
Section: Methodscontrasting
confidence: 51%
“…red) but not if the stimulus is in another colour (e.g. green ;Folk, Leber, & Egeth, 2002), a result which we replicated and extended in our laboratory (Leblanc & Jolicoeur, 2005). Such results demonstrate that attention control settings can exert a top-down influence on the degree to which bottom-up signals can capture spatial attention.…”
Section: Introductionsupporting
confidence: 57%
“…Bauer, Jolicoeur, & Cowan, 1996;Nagy & Sanchez, 1990). Furthermore, colour singletons appear to draw spatial attention to their location when subjects maintain the intention to find targets of that colour (Folk, Leber, & Egeth, 2002;Leblanc & Jolicoeur, 2005). In the latter case, the attentional capture effects appeared to take place automatically (once top-down attentional control settings were adopted by the subjects), given that the capture by the distractor always produced a decrement in report of the desired target.…”
Section: Discussionmentioning
confidence: 86%
“…The magnitude of the spatial blink was approximately constant from lag 1 to lag 3 (corresponding to intervals of 80-240 msec) in the present experiment. Although some researchers have reported greater spatial blink magnitudes at lag 2 than at other lags (Folk et al, 2002, corresponding to a 168-msec delay; Lamy et al, 2004, 200 msec), others have found that the spatial blink effect peaked at lag 1 (Leblanc & Jolicoeur, 2005, 117 msec) and decreased as lag increased. It is possible that these differences are due to unique visual properties of the stimuli, such as the eccentricity and size of the distractors.…”
Section: Synergy Between Stimulus-driven Salience and Goal-driven Primentioning
confidence: 98%